PARASITE COMMUNITIES OF THE TRAMBOLLO, LABRISOMUS PHILIPPII (STEINDACHNER, 1866) (PERCIFORMES: LABRISOMIDAE), OFF COASTAL ZONE OF CHORRILLOS, LIMA, PERU - Iannacone, José (2011)
Labrisomus philippii (Steindachner, 1866) is a marine fish species of intertidal-subtidal rocky bottom with distribution on the coast of Peru and Chile. 124 specimens of L. philippii were acquired in the Chorrillos Fishmarket, Lima, Peru, between May to September 2008 to evaluate parasitefauna infracommunities. Fish showed a mean length of 19.1 cm (10 cm to 24.5 cm). Parasites were collected and counted employing conventional techniques. Parasite assemblages were higher for endoparasite (99.3%) than ectoparasites abundance (0.70%). The mean parasite species richness as 1.1 (0-5). Forty-seven hosts were not parasited and seventy-seven hosts showed infection at least with one parasite specie. Eight parasites with the following prevalence and mean abundance were found: an unidentified mixosporea (7.2%; 0.1±0.5), the copepod Acanthochondria syciasis (Kroyer, 1863) (4%; 0.04±0.2), three trematods, Zoogonus rubellus (Olsson, 1868) (32.2; 18.4±128.9), Prosorhynchoides rioplatensis (Szidat, 1970) Lunaschi, 2003 (30.6%; 3.6±12.1), and Helicometra fasciata (Rudolphi, 1819) (13.7%; 4.7±19.4), the larval acanthocephala Corynosoma australe Johnston, 1937 (15.3%; 0.5±2.0), the nematode Proleptus sp. (2.4%; 0.02± 0.1) and a Piscicolidae unidentified gen. specie (1.6%; 0.02± 0.1). Importance concept of Bursey showed that Z. rubellus (1872), H. fasciata (483.7) and P. rioplatensis (390) presented high numeric values. Five of the eight parasites showed an aggregated distribution. Finally, the results obtained of community parasite structure registered on L. philippii twenty years ago in the same locality of study were compared.